2010
DOI: 10.1007/s00264-010-1103-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascularised fibular graft for the treatment of congenital pseudarthrosis of the tibia: long-term complications in the donor leg

Abstract: Treatment of congenital pseudarthrosis of the tibia is still controversial, and vascularised fibula graft is a reliable method for consolidation, although complications can occur in the donor leg after fibula grafting. This study evaluates 16 patients with congenital pseudarthrosis of the tibia (CPT) treated with contralateral fibular graft, with regard to complications in the donor leg, and assesses the influence of distal tibiofibular joint arthrodesis in these complications. All patients with CPT were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Common complications of donor region reported are surgical scar, pain, ankle instability, motor-neural weaknesses, proximal migration of fibula, ankle valgus and deformities of the tibial shaft and ankle [11][12][13][14][15][16][17]. The recommendations of leaving a distal fibular remnant greater than 5-6 cm, distal tibiofibular arthodesis, and scheduling surgical harvest at age older than eight years emerged from these findings [11][12][13][14]. A close examination of literature on the subject showed that a majority of these results surfaced from vascularized fibula graft series where regeneration of donor fibula did not occur.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Common complications of donor region reported are surgical scar, pain, ankle instability, motor-neural weaknesses, proximal migration of fibula, ankle valgus and deformities of the tibial shaft and ankle [11][12][13][14][15][16][17]. The recommendations of leaving a distal fibular remnant greater than 5-6 cm, distal tibiofibular arthodesis, and scheduling surgical harvest at age older than eight years emerged from these findings [11][12][13][14]. A close examination of literature on the subject showed that a majority of these results surfaced from vascularized fibula graft series where regeneration of donor fibula did not occur.…”
Section: Discussionmentioning
confidence: 98%
“…There are only a few studies in the pediatric population to testify for above inferences. Moreover, the main literature for donor site follow-up in the paediatric group has emerged from the vascularized fibular graft technique [11][12][13][14][15][16][17]. An important difference between vascularized and non-vascularized fibular graft is that the donor site following the latter regenerates new bone provided periosteum is preserved, and it can even be used for reharvest.…”
Section: Introductionmentioning
confidence: 98%
“…Ben Amotz et al 20 demonstrated that the majority of patients had temporary motor dysfunction of peroneal nerve and only 2.6% were permanent. Additionally, the complications in donor site, mainly ankle valgus and proximal migration of the lateral malleolus, could also result in unbalanced force of tibia and instability of ankle joint, which could be prevented by reconstruction of proximal tibia with tibiofibular syndesmotic screw, tibial autograft, prosthesis or artificial bone graft [21][22][23] . In our study, peroneal palsy and foot drop occurred temporarily and were self-restoring, and no associated complication occurred in donor site after reconstruction with an allograft proactively.…”
Section: Discussionmentioning
confidence: 99%
“…The free vascularized fibular flap is a reliable technique for reconstruction of bone defects, usually larger than 6 cm, and indications includes: limb reconstruction after tumor, trauma, infection and congenital deformities. 5 , 6 , 7 Taylor et al 4 describes 38 free vascularized fibular flaps for tibial reconstruction, observing that, stress fractures before consolidation, occurs in most cases and obtain an overall success rate of 95%, with vascularized bone flaps. The complications described to vascularized fibular flaps includes: thrombosis of vessels anastomoses, infection, pseudarthrosis and inadequate graft hypertrophy, and can lead to limb amputation in these severe cases.…”
Section: Discussionmentioning
confidence: 99%